Leibniz and his correspondents - Lodge, Paul, 1968- (New York : Cambridge University Press, 2004)
Unlike most of the other great philosophers Leibniz never wrote a magnum opus, so his philosophical correspondence is essential for an understanding of his views. This collection of new essays by pre-eminent figures in the field of Leibniz scholarship is the most thorough account of Leibniz's philosophical correspondence available. It both illuminates Leibniz's philosophical views and pays due attention to the dialectical context in which the relevant passages from the letters occur. The result is a book of enormous value to all serious students of early-modern philosophy and the history of ideas.